Мonitoring the sustainability of small and medium business in the regions of Ukraine based on the resource approach - Mariia Bieloborodova; Svitlana Bessonova; Anna Bessonova; Бєлобородова Марія; Бессонова Світлана; Бессонова Анна (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2022)
Abstract. The features of small and medium business in Ukraine require an integrated approach to sustainability management, which includes taking into account the positions of key stakeholders and their resource contribution to business activities. The main guideline in sustainability provision is the detection and scanning of social requirements, as well as adequate and timely response to the stakeholders’ requests. The purpose of the research is to monitor the level of imbalance of resource exchange between small and medium business and its key stakeholders in the regions of Ukraine. The following methods were used in the research: focus groups survey, statistical generalization, correlation-regression analysis, linear modeling, and graphical method. Based on the results of modeling the resource interaction of small and medium business with the main stakeholders, the vectors of the "ideal" and "real" resource exchange structure were constructed. The difference in the structures of these vectors reflects the imbalance of the existing resource exchange in the system, which can be expressed by the ratio of imbalance. The smaller the value of this ratio, the more balanced is resource exchange. It is proved that small businesses have an increased need for strong personal relationships with the local community and authorities. It is important for companies to identify the importance of stakeholders according to their resource contribution. To form a strategy of sustainability it is necessary to understand which of the stakeholders’ groups make the greatest contribution to the imbalance between the "ideal" and "real" resource exchange structure. The study shows that social responsibility is important not only for the internal policy of the business entity, but also when interacting with external environment, with stakeholders, both private and government, business partners. Only a responsibility for own and partner activities at each stage of communication can guarantee further synergy of results. Regional features of social development processes require appropriate measures of administrative regulation aimed at creating appropriate conditions for stimulating the social activity of small and medium businesses. The main direction of development of the modern regional development strategy is the priority of public needs.

Резюме. Особливості малого та середнього бізнесу в Україні вимагають комплексного підходу до управління стійкістю, який передбачає врахування позицій ключових стейкхолдерів та їх ресурсного внеску в бізнес-діяльність. Основним орієнтиром у забезпеченні сталості є виявлення та сканування соціальних вимог, а також адекватне та своєчасне реагування на запити зацікавлених сторін. Метою дослідження є моніторинг рівня дисбалансу обміну ресурсами між малим і середнім бізнесом та його ключовими стейкхолдерами в регіонах України. У дослідженні використовувалися такі методи: опитування фокус-груп, статистичне узагальнення, кореляційно-регресійний аналіз, лінійне моделювання, графічний метод. За результатами моделювання ресурсної взаємодії малого та середнього бізнесу з основними стейкхолдерами побудовано вектори «ідеальної» та «реальної» структури ресурсообміну. Різниця в структурах цих векторів відображає незбалансованість існуючого обміну ресурсами в системі, яка може бути виражена коефіцієнтом незбалансованості. Чим менше значення цього коефіцієнта, тим більш збалансований обмін ресурсами. Доведено, що малий бізнес має підвищену потребу в міцних особистих стосунках з місцевою громадою та владою. Для компаній важливо визначити важливість зацікавлених сторін відповідно до їх внеску ресурсів. Для формування стратегії стійкості необхідно зрозуміти, яка з груп стейкхолдерів вносить найбільший внесок у дисбаланс між «ідеальною» та «реальною» структурою обміну ресурсами. Дослідження показує, що соціальна відповідальність важлива не лише для внутрішньої політики суб’єкта господарювання, а й при взаємодії із зовнішнім середовищем, із зацікавленими сторонами, як приватними, так і державними, бізнеспартнерами. Лише відповідальність за свою та партнерську діяльність на кожному етапі комунікації може гарантувати подальшу синергію результатів. Регіональні особливості процесів суспільного розвитку потребують відповідних заходів адміністративного регулювання, спрямованих на створення належних умов для стимулювання соціальної активності малого та середнього бізнесу. Основним напрямком розробки сучасної стратегії регіонального розвитку є пріоритет суспільних потреб.

Az ukrajnai kis- és középvállalkozások sajátosságai megkövetelik a fenntarthatósági menedzsment átfogó ismeretét, amely magában foglalja a kulcsfontosságú érdekelt felek pozícióinak és az üzleti tevékenységekhez való erőforrás-hozzájárulásának figyelembevételét. A fenntarthatóság biztosításának fő irányvonala a társadalmi követelmények azonosítása és átvilágítása, valamint az érdekelt felek kérésének megfelelő és időben történő reagálása. A tanulmány célja a kis- és középvállalkozások, valamint kulcsfontosságú érintettjeik közötti erőforrás-csere egyensúlyhiányának nyomon követése Ukrajna régióiban. A kutatás az alábbi módszereket alkalmazta: fókuszcsoportos felmérés, statisztikai általánosítás, korreláció-regresszió elemzés, lineáris modellezés, grafikus módszer. A kis- és középvállalkozások erőforrás-kölcsönhatásainak a fő érintettekkel való modellezésének eredményei alapján megszerkesztették az „ideális” és a „valós” erőforráscserestruktúra vektorait. Ezen vektorok szerkezetének különbsége a rendszerben meglévő erőforráscsere egyensúlyhiányát tükrözi, amelyet az egyensúlyi együtthatóval fejezhetünk ki. Minél kisebb ennek az együtthatónak az értéke, annál kiegyensúlyozottabb az erőforrások cseréje. Bebizonyosodott, hogy a kisvállalkozásoknak fokozottan van szükségük erős személyes kapcsolatokra a helyi közösségekkel és hatóságokkal. Fontos, hogy a vállalatok a stakeholderek jelentőségét az erőforrásokhoz való hozzájárulásuk alapján határozzák meg. A fenntarthatósági stratégia megfogalmazásához meg kell érteni, hogy az érdekelt csoportok közül melyik járul hozzá leginkább az „ideális” és a „valós” erőforráscsere-struktúra közötti egyensúlyhiányhoz. A tanulmány azt mutatja, hogy a társadalmi felelősségvállalás nemcsak a gazdálkodó egység belső politikája szempontjából fontos, hanem a külső környezettel, a magán- és állami érdekelt felekkel, üzleti partnerekkel való interakció során is. Csak a saját és a partner tevékenységéért való felelősség garantálhatja a kommunikáció minden szakaszában a további eredmények szinergiáját.
Моніторинг стійкості малого та середнього бізнесу в регіонах України на основі ресурсного підходу
A kis- és középvállalkozások fenntarthatóságának nyomon követése Ukrajna régióiban az erőforrás megközelítés alapján
https://aab-economics.kmf.uz.ua/aabe/issue/view/1
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00010507
Keywords: stakeholders; sustainability; social responsibility; business management; resource exchange